2005
DOI: 10.1093/humrep/deh767
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of leptin and C-reactive protein in serum and follicular fluid during assisted reproductive cycles

Abstract: Leptin and C-reactive protein levels change significantly during assisted reproductive treatment. In contrast to estradiol they are, however, not a marker of success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
4

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 29 publications
4
35
4
Order By: Relevance
“…In the present study, we have failed to observe any statistically significant correlation between day 3 hs-CRP and IVF cycle outcomes or clinical pregnancy. Our findings concur with other studies [19,20] which found no correlation between circulating levels of hs-CRP prior to ovarian stimulation with gonadotrophins and IVF outcome. In contrast, Levin and colleagues [17], who measured hs-CRP at different time points, noted that hs-CRP concentrations on day 3 correlated with IVF treatment failure.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In the present study, we have failed to observe any statistically significant correlation between day 3 hs-CRP and IVF cycle outcomes or clinical pregnancy. Our findings concur with other studies [19,20] which found no correlation between circulating levels of hs-CRP prior to ovarian stimulation with gonadotrophins and IVF outcome. In contrast, Levin and colleagues [17], who measured hs-CRP at different time points, noted that hs-CRP concentrations on day 3 correlated with IVF treatment failure.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, adipose tissue is a potent source of inflammatory interleukins and other circulating cytokines, the secretion of which increase with adiposity [25][26][27]. In agreement with previous studies [20,28], we have found a significant correlation between basal hs-CRP and BMI. Furthermore, although the mean BMI of women who conceived was higher than those who had a unsuccessful cycle (26.3±3.15 and 25.0±2.68 kg/m 2 ), this failed to reach statistical significance.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations